Design and Analysis of Cylindrical Antiresonant Reflecting Optical Waveguide - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2003)
A field-transfer matrix method is developed to analyze the modal characteristics of cylindrical multilayered waveguides with axis-symmetric geometry. A new design rule for cylindrical antiresonant reflecting optical waveguides (ARROWs), based on a three-step design process, is also proposed to minimize the radiation loss of the fundamental leaky mode. In addition, a simple approach is suggested to estimate the optimum core diameter of the cylindrical ARROWs for optimum radiation loss and radiation loss margin. Hence, it can be shown that an extra high index cladding layer is good enough to reduce the radiation loss as well as to maintain a reasonably high radiation loss margin in simplified ARROWs for long wavelength application.